# How do you solve -1/2(b+2)+3b=-1?

Jul 21, 2018

Work backwards combine like terms and solve.

#### Explanation:

The opposite of PEMDAS is PESADM

 -1/2 ( b +2) + 3b = -1 ;- 1/2 xx b + -1/2 xx 2 + 3b = -1
b -1
This is the result of the distributive property

$- \frac{1}{2} b + - \frac{1}{2} \times 2 + 3 b = - 1 : = - \frac{1}{2} b + - 1 + 3 b = - 1$

Using the communicative property to combine like terms gives

$- \frac{1}{2} b + 3 b - 1 = - 1$

Combing like terms gives.

$2 \frac{1}{2} - 1 = - 1$

Adding + 1 to both sides gives.

$2 \frac{1}{2} b - 1 + 1 = - 1 + 1$

The result is

$2 \frac{1}{2} b = 0$

dividing both sides by 2 1/2 gives

$\frac{2 \frac{1}{2} b}{2 \frac{1}{2}} = \frac{0}{2 \frac{1}{2}}$

$b = 0$

Jul 21, 2018

$b = 0$

#### Explanation:

Let's distribute the $- \frac{1}{2}$ to both terms to get

$- \frac{1}{2} b - 1 + 3 b = - 1$

We can combine like terms on the left to get

$2.5 b - 1 = - 1$

Adding $1$ to both sides gives us

$\frac{2}{5} b = 0$

Dividing both sides by $2.5$, we get

$b = 0$

Hope this helps!